Evaluating of image sponsoring in football: Focusing on attitudes - Berkes, P.; Nyerges, M. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this study was to evaluate the common image characteristics between a professional Hungarian football club and its sponsor company product (soft drink) and create a theoretical image-sponsoring model. Two research questions have been designed: 1) Has a significant different between the sponsor (product) and sponsored (club) image attributes among the subjects? 2) Could the sport consumers identify the common image features in the two groups?